1997
DOI: 10.1542/peds.100.5.841
|View full text |Cite
|
Sign up to set email alerts
|

Infant Arousals During Mother-Infant Bed Sharing: Implications for Infant Sleep and Sudden Infant Death Syndrome Research

Abstract: Routinely bed sharing infants also exhibited more frequent TAs in stage 3-4 than the routine solitary sleepers in both conditions. In both groups, the number of infant arousals (EWs ؉ TAs) that overlapped the mother's was doubled during bed sharing, with infant arousals leading most often.Conclusions. Mother-infant bed sharing promotes infant arousals. Together with a previous report that bed sharing reduces stage 3-4 sleep, this suggests that normative values for infant sleep must be interpreted within the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 49 publications
1
82
0
3
Order By: Relevance
“…This heightened sensitivity might increase the chances that mothers could more quickly detect and intervene against a life threatening event that night-time separation from the baby precludes. 19,20 Three major epidemiological studies have shown that when a committed caregiver, usually the mother, sleeps in the same room but not in the same bed with their infant the chance of the infant dying from sudden infant death syndrome (SIDS) is reduced by 50%. [21][22][23] This protective factor does not generalise to co-sleeping in proximity to siblings.…”
Section: Introductionmentioning
confidence: 99%
“…This heightened sensitivity might increase the chances that mothers could more quickly detect and intervene against a life threatening event that night-time separation from the baby precludes. 19,20 Three major epidemiological studies have shown that when a committed caregiver, usually the mother, sleeps in the same room but not in the same bed with their infant the chance of the infant dying from sudden infant death syndrome (SIDS) is reduced by 50%. [21][22][23] This protective factor does not generalise to co-sleeping in proximity to siblings.…”
Section: Introductionmentioning
confidence: 99%
“…(4,5) As the rate of prone positioning has declined, other previously unrecognized risk factors for sudden unexplained infant death have emerged in recent epidemiologic studies. Despite the fact that bedsharing between an infant and adult facilitates breastfeeding and enhances parent-infant interactions, (6,7) this sleeping arrangement has been identified in epidemiologic studies as being hazardous in certain situations, particularly when one or both parents are smokers, (8)(9)(10)(11)(12) on excessively soft surfaces, such as waterbeds, sofas, and armchairs, (9,10,(13)(14)(15) or when the infant is less than 2-3 months of age. (9,12,(14)(15)(16)(17) In addition, there is an increased risk for sudden unexpected infant death when there are multiple bedsharers (13) and when bedsharing occurs for the entire night.…”
mentioning
confidence: 99%
“…Co-sleeping mothers and infants have demonstrated synchrony in their sleep patterns, facilitating simultaneous arousals and frequent bouts of breastfeeding Mosko et al, 1997;Ball & Ward Platt, 2007). By sharing sleep, the infant"s basic need for physical closeness and frequent, short feeding episodes is optimally met while the mother gets more rest.…”
Section: Discussionmentioning
confidence: 99%